Continuous negative-to-positive tuning of thermal expansion achieved by controlled gas sorption in porous coordination frameworks. Issue 1 (December 2018) - Auckett, Josie; Barkhordarian, Arnold; Ogilvie, Stephen; Duyker, Samuel; Chevreau, Hubert; Peterson, Vanessa; Kepert, Cameron
Abstract Control of the thermomechanical properties of functional materials is of great fundamental and technological significance, with the achievement of zero or negative thermal expansion behavior being a key goal for various applications. A dynamic, reversible mode of control is demonstrated for the first time in two Prussian blue derivative frameworks whose coefficients of thermal expansion are tuned continuously from negative to positive values by varying the concentration of adsorbed CO2 . A simple empirical model that captures site-specific guest contributions to the framework expansion is derived, and displays excellent agreement with the observed lattice behaviour. Achieving control over the thermomechanical properties of functional materials is desirable, yet remains highly challenging. Here, the authors demonstrate continuous negative-to-positive tuning of thermal expansion in two Prussian blue analogues, by varying the concentration of adsorbed CO2 .